Germline fate determination by a single ARGONAUTE protein in Ectocarpus - Viktoriia Bukhanets; Rita A. Batista; Fabian B. Haas; Rémy Luthringer; Jumana Kushkush; Min Zheng; Katharina Hipp; Vikram Alva; Claudia Martinho; Susana M. Coelho (Proceedings of the National Academy of Sciences, 2026)
ARGONAUTE (AGO) proteins are a highly conserved family of RNA-binding proteins that play central roles in gene regulation and developmental processes across eukaryotes. Although AGO family members have been extensively studied in animals and plants, where they are typically encoded by multiple genes, their function in brown algae, a diverse and complex group of multicellular algae, remains largely unknown. Here, we show that the genomes of several brown algae encode only a single AGO protein, containing the conserved functional domains characteristic of the family. Using the model brown alga Ectocarpus and a combination of cell biology, genetic, and transcriptomic approaches, we demonstrate that AGO is essential for the transition from vegetative growth to sexual reproductive development and for germline establishment. Our results further suggest that AGO functions in concert with microRNAs to regulate target genes primarily at the posttranscriptional level, likely through translational repression. Ectocarpus thus represents a rare example of a complex multicellular organism that relies on a single AGO protein to regulate key developmental processes, pointing to a minimalistic model of RNA-based regulation in brown algae.